2003
DOI: 10.1128/jb.185.19.5882-5890.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Outer Membrane Protein, Wzi, Is Involved in Surface Assembly of theEscherichia coliK30 Group 1 Capsule

Abstract: Escherichia coli group 1 K antigens form a tightly associated capsule structure on the cell surface. Although the general features of the early steps in capsular polysaccharide biosynthesis have been described, little is known about the later stages that culminate in assembly of a capsular structure on the cell surface. Group 1 capsule biosynthesis gene clusters (cps) in E. coli and Klebsiella pneumoniae include a conserved open reading frame, wzi. The wzi gene is the first of a block of four conserved genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 57 publications
0
62
0
Order By: Relevance
“…This locus is present in all capsular types of K. pneumoniae, and different wzi locus sequences are strongly associated with specific K antigens. The wzi gene encodes a surface protein involved in capsule attachment to the outer membrane, where the loss of this protein results in essentially acapsular bacteria (211,212). wzy, also known as orf4, is involved in the polymerization of capsular polysaccharides, while wza, wzc, orf5, and orf6 are involved in their surface assembly (202,213).…”
Section: Capsulementioning
confidence: 99%
“…This locus is present in all capsular types of K. pneumoniae, and different wzi locus sequences are strongly associated with specific K antigens. The wzi gene encodes a surface protein involved in capsule attachment to the outer membrane, where the loss of this protein results in essentially acapsular bacteria (211,212). wzy, also known as orf4, is involved in the polymerization of capsular polysaccharides, while wza, wzc, orf5, and orf6 are involved in their surface assembly (202,213).…”
Section: Capsulementioning
confidence: 99%
“…The cps locus has a mosaic structure, with a group of six conserved genes (galF, orf2, wzi, wza, wzb, and wzc) at its 5= end. Among these, the wzi gene codes for the outer membrane protein Wzi, which is involved in attachment of the capsular polysaccharide to the outer membrane (27,28). The objective of this study was to evaluate the sequence polymorphisms of the wzi gene for strain typing and for inference of the serotypes of K. pneumoniae clinical isolates.…”
mentioning
confidence: 99%
“…However, in contrast to LPS, G4Cs are composed of a high-molecular-weight polysaccharide attached to the bacterial surface not via lipid but probably by interaction with a specific surface protein(s) (29). We previously showed that EPEC O127:H6 expresses the etk gene, which encodes a protein tyrosine kinase (17).…”
mentioning
confidence: 99%